(untitled) (Revista Iberoamericana de Bioética, 2022)
The purpose of this study is to describe the social conditions of the elderly in Mexico, in light of the World Health Organization’s declaration of the Decade of Healthy Ageing. Mexico has approximately 15.1 million people aged 60 and over, making up 12% of the country’s population. This will have consequences in the social arena, as well as in the governmental structures to award action programmes that favour providing adequate care for the elderly, within the framework of human rights. In this regard, in Mexico there is a deep commitment to strengthen public policy in this area. However, there are still older adults — women and men — in conditions far from healthy ageing.